The appearance of common turkic phrasemes in modern turkic languages (Eurasian Journal of Philology Science and Education, 2023)
In the article, a comparative-historical analysis of phrasemes with a somatic component is carried out. Consideration of phrasemes within the framework of Turkic studies helps to identify similarities and features of linguistic units. Therefore, consideration of phrasemes using a comparative-historical method is one of the most urgent issues of modern science. In the course of the research, the collection and systematization of linguistic units from lexicographic sources was carried out. In the article, grammatical and semantic features of the ancient Turkic phrasemes, which are motivated by somatism of the head, ears, eyes are described, also their usage in modern Turkic languages were considered, and the researchers’ own opinion was given in this regard. During the study, the semantics of the lexemes in the phraseme were considered.The involvement of various tribes in the ethnogenesis of each modern Turkic people can be seen in the process of considering linguistic units. Therefore, when studying phrasemes from a diachronic point of view, it is important to consider not only the group of related languages but also the location area of Turkic tribes (from the areal point of view). In the article, the name common Turkic phrasemes is used to denote the phrasemes found in written monuments before the XV century. During the study of phrasemes, it was found that common Turkic phrasemes are still in use in modern Turkic languages, their grammatical and semantic features were formed according to the development of national languages. As a result of the structural and semantic analysis of common Turkic phrasemes, it was found that some ancient phrasemes have fallen out of use. Phrasemes are special linguistic units describing the cultural code, caused by various internal and external factors during the development of national languages.